2018
DOI: 10.1111/mmi.14085
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli and Pseudomonas aeruginosa lipopolysaccharide O‐antigen ligases share similar membrane topology and biochemical properties

Abstract: WaaL is an inner membrane glycosyltransferase that catalyzes the transfer of O-antigen polysaccharide from its lipid-linked intermediate to a terminal sugar of the lipid A-core oligosaccharide, a conserved step in lipopolysaccharide biosynthesis. Ligation occurs at the periplasmic side of the bacterial cell membrane, suggesting the catalytic region of WaaL faces the periplasm. Establishing the membrane topology of the WaaL protein family will enable understanding its mechanism and exploit it as a potential ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
(112 reference statements)
1
18
0
Order By: Relevance
“…Cells lacking WzzE are known to lose modality in the ECA polymer, giving rise to a more random distribution of chain lengths (Barr et al, 1999). We validated this observation; there are relatively higher levels of shorter chain ECA, presumably including Lipid III ECA precursors, in the ∆wzzE It has previously been reported that the terminal GlcNAc moiety attached to the E. coli K-12 LPS core oligosaccharide is derived from und-PP-GlcNAc (i.e., Lipid I ECA ) via the action of WaaL (Feldman et al, 1999;Ruan et al, 2018). Since WaaL accepts different und-PP-linked substrates, it may be possible that corresponding modifications of LPS can occur in strains accumulating Lipid II/III ECA ; these modified LPS might contribute to restored OM barrier function in the tol-pal mutants.…”
Section: Accumulation Of Eca Intermediates Along the Biosynthetic Psupporting
confidence: 71%
See 1 more Smart Citation
“…Cells lacking WzzE are known to lose modality in the ECA polymer, giving rise to a more random distribution of chain lengths (Barr et al, 1999). We validated this observation; there are relatively higher levels of shorter chain ECA, presumably including Lipid III ECA precursors, in the ∆wzzE It has previously been reported that the terminal GlcNAc moiety attached to the E. coli K-12 LPS core oligosaccharide is derived from und-PP-GlcNAc (i.e., Lipid I ECA ) via the action of WaaL (Feldman et al, 1999;Ruan et al, 2018). Since WaaL accepts different und-PP-linked substrates, it may be possible that corresponding modifications of LPS can occur in strains accumulating Lipid II/III ECA ; these modified LPS might contribute to restored OM barrier function in the tol-pal mutants.…”
Section: Accumulation Of Eca Intermediates Along the Biosynthetic Psupporting
confidence: 71%
“…However, since deletion of either wecA (does not restore OM barrier the GlcNAc moiety from und-PP-GlcNAc (Lipid I ECA ) can itself be transferred onto LPS in a WaaL-dependent manner (Feldman et al, 1999;Ruan et al, 2018). We reasoned it is likely that the incomplete sugar subunits on Lipid II/III ECA could also be ligated onto LPS, therefore, affecting the physical properties of the OM via LPS modification.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequences of WaaL ligases are not highly conserved, but they are all predicted integral IM proteins with eight or more TMH (Raetz and Whitfield, 2002). The WaaL ligases of Pseudomonas aeruginosa and E. coli (WaaL Pa and WaaL Ec respectively) contain a partially periplasmic Wzy_C domain, responsible for catalytic activity and 12 TMHs (Islam et al, 2010;Pan et al, 2012;Ruan et al, 2012;Ruan et al, 2018) ( Fig. 1E).…”
Section: Identification Of Phpt and Ligase Candidates For Lps O-antigmentioning
confidence: 99%
“…However, since deletion of either wecA (does not restore OM barrier function) or other wec genes (restore OM barrier function) would result in the loss of full length ECALPS, we ruled out the role of ECALPS in rescuing the OM permeability defect. It has been reported that the GlcNAc moiety from und-PP-GlcNAc (Lipid I ECA ) can itself be transferred onto LPS in a WaaL-dependent manner (Feldman et al, 1999;Ruan et al, 2018). We reasoned it is likely that the incomplete sugar subunits on Lipid II/III ECA could also be ligated onto LPS, therefore affecting the physical properties of the OM via LPS modification.…”
Section: Discussionmentioning
confidence: 98%
“…It has previously been reported that the terminal GlcNAc moiety attached to the E. coli K-12 LPS core oligosaccharide is derived from und-PP-GlcNAc (i.e. Lipid I ECA ) via the action of WaaL (Feldman et al, 1999;Ruan et al, 2018). Since WaaL accepts different und-PP-linked substrates, it may be possible that corresponding modifications of LPS can occur in strains accumulating Lipid II/III ECA ; these modified LPS might contribute to restored OM barrier function in the tol-pal mutants.…”
Section: Accumulation Of Eca Intermediates Along the Biosynthetic Patmentioning
confidence: 99%